KEARIFAN TRADISI ISLAM INDONESIA DALAM HIIFZ AL-BI'AH - Ahmad, Maghfur (IBDA` : Jurnal Kajian Islam dan Budaya, 2012)
This article discusses and analyzes the wisdom in Islam tradition,the juridical implementation and the application of law on protecting theenvironment in Indonesia. The Islamic tradition emphasizes on man’ mainduty; serve the God by keep and protect His creature. The data are collectedby documentation method and they are read by historical analysisand transcendence-structuralism. This article shows that the environmentparadigm and ideology is based on affection principle (rah}mah). The loveto nature in Islamic tradition is brought into reality by harmonizingbehaviour (tawa>zun), between personal right and environment’s right. Manmay take advantages from the nature but in a good way. Muslims still on‘pseudo-love’ condition because they still give priority to themselves onobeying the law.